1993
DOI: 10.1002/bjs.1800801223
|View full text |Cite
|
Sign up to set email alerts
|

Repeat hepatectomy for cancer

Abstract: In a series of 279 hepatectomies performed for cancer between June 1984 and March 1992, 46 were repeat operations, for metastases in 41 patients. The primary tumour was in the colon and rectum (28 patients), APUDoma (five) and miscellaneous (eight). Repeat hepatectomies were performed in 26 per cent of patients who had recurrence after the first liver resection and in 40 per cent of those who had liver recurrence. An unsuspected extrahepatic recurrence was discovered and resected in eight instances and in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 10 publications
4
46
1
Order By: Relevance
“…6'7"12"16" 9 Ten to 40% of these patients with isolated recurrence undergo second resections. 12,14,16,19,21 In our experience, 71% of patients recurred at a mean of 13 months, 55% involving the liver and 33% involving the liver alone. Nineteen percent of those with isolated recurrence underwent a second hepatic operation.…”
Section: Resultsmentioning
confidence: 99%
“…6'7"12"16" 9 Ten to 40% of these patients with isolated recurrence undergo second resections. 12,14,16,19,21 In our experience, 71% of patients recurred at a mean of 13 months, 55% involving the liver and 33% involving the liver alone. Nineteen percent of those with isolated recurrence underwent a second hepatic operation.…”
Section: Resultsmentioning
confidence: 99%
“…Repeat hepatectomy is the gold standard for treating recurrent liver metastases (16)(17)(18) with reported low local recurrence. However, repeat hepatectomy is technically demanding, with a mortality rate close to 2% (17).…”
Section: Discussionmentioning
confidence: 99%
“…the exact place of RFA in the treatment of recurrent liver metastases is still debated because there is no solid evidence on the impact of RFA on overall recurrence and long-term survival. Repeated surgery, when amenable, is still considered the first treatment option in that setting (14)(15)(16)(17)(18), but the risk of complications is higher than after primary liver resection. therefore, percutaneous RFA could be an attractive alternative treatment in selected patients with recurrent CLM due to its lower mortality and morbidity rates.…”
Section: Introductionmentioning
confidence: 99%
“…89,90,[93][94][95] As the safety and efficacy of liver resection has been increasingly accepted, repeat resections are also more commonly being performed. Although re-resections only account for 3% to 11% of all liver resections in experienced centers, [94][95][96][97] the number of repeat resections at major centers may be increasing. Bismuth et al 93 reported a significant increase in the percent of liver resections that are repeat resections at their institution from 6% (6 of 105) from 1983 to 1989 compared with 28% (49 of 177) from 1990 to 1994.…”
Section: Results Of Liver Resection For Colorectal Metastasesmentioning
confidence: 99%
“…Postoperative complications range from 15% to 32%, somewhat higher when compared with initial resections. [94][95][96] This higher morbidity is in part the result of increased risk for bleeding related to perihepatic adhesions and the frequent limited ability to achieve selective vascular control. The selection criteria of patients for re-resection for colorectal liver metastases are similar to those for initial resection.…”
Section: Results Of Liver Resection For Colorectal Metastasesmentioning
confidence: 99%